1996
DOI: 10.1057/palgrave.jibs.8490150
|View full text |Cite
|
Sign up to set email alerts
|

Expatriate Performance Appraisal in U.S. Multinational Firms

Abstract: This exploratorystudy examines empiricallyexpatriate performance appraisal (EPA)practicesforU.S. multinational firmsand assesseshowsuchpracticesrelateto the perceivedaccuracyof EPAs. Froma sampleof U.S.multinationals, theresultssuggestthata balanced set of ratersfromhostandhomecountriesandmorefrequent appraisals relatepositivelyto perceived accuracyof EPAs.Thedatasuggest,however, that most respondentfirms did not follow these practices.In addition, the use of standardized andcustomizedEPAevaluationforms relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 20 publications
1
96
0
1
Order By: Relevance
“…An example of a contextual criterion would be the general economic climate for an expatriate who needs to sign an important contract with a local contractor. Although contextual criteria were not perceived to be positively related to expatriate performance appraisal accuracy in the study conducted by Gregersen et al (1996), such criteria undoubtedly work to constrain or facilitate the expatriate's performance. It would be prudent for future researchers employing multidimensional operationalizations of expatriate job performance to address this issue as it relates to the performance dimensions at hand.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…An example of a contextual criterion would be the general economic climate for an expatriate who needs to sign an important contract with a local contractor. Although contextual criteria were not perceived to be positively related to expatriate performance appraisal accuracy in the study conducted by Gregersen et al (1996), such criteria undoubtedly work to constrain or facilitate the expatriate's performance. It would be prudent for future researchers employing multidimensional operationalizations of expatriate job performance to address this issue as it relates to the performance dimensions at hand.…”
Section: Discussionmentioning
confidence: 62%
“…Because most studies seem to have employed male American expatriates stationed in Asia, further research should endeavor to include samples that are more diverse so that findings may be generalized across all members of the expatriate population. Finally, Gregersen, Hite, and Black (1996) have pointed to the importance of contextual criteria. These result from the situation in which the expatriate is performing and pertain to factors that are beyond his or her control.…”
Section: Discussionmentioning
confidence: 99%
“…: Miller, 1977, Gregersen et al, 1996Shay and Baack, 2004), liminal situations are characterised by a clear set of features, as we have seen above, that are easily recognised by the actors involved. Given the developmental potential of liminality, we suggest that expatriates would benefit if they were aware of the formal existence of liminality.…”
Section: Recognising Liminalitymentioning
confidence: 92%
“…On the other hand, the global integration about International Human Resource Management (IHRM) is also required for a multinational firm at the same time. The trait with which IHRM differs from human resource management (HRM) for a national corporation is coping with the complexity of performing the tune-up across the border through overseas relocation of business modality or management practices for the human resource of two or more countries (e. g., Dowling, 1988;De Chieri & Dowling, 2006;De Cieri et al, 2001;Gregersen & Black, 1996;Morgan, 1986). Franko (1973) has indicated that an executive person's nationality politics in a global corporation changes with the phase of an internationalisation of a company based on the investigation of actual conditions of a European and American company.…”
Section: -1 Human Resource Management Of a Multinational Firmmentioning
confidence: 99%